Some aspects of the Franco-German economic relations between the two world wars - Wolf, Hans J (Rhodes University, Faculty of Commerce, Department of Economics, 1970)
From Preface: In this thesis I have aimed at covering a field in Economic History where not many suitable publications are available in English. During the interwar period, the maintenance of peace and harmonious international relations was directly dependent on a reconciliation of the conflicting interests between France and Germany. In studying the economic implications of the Franco-German antagonism, I have tried to throw light upon the crucial role which this relationship played. The Appendix offers a quantitative survey of economic conditions in the two countries and of the relevant production and exchange problems. To assist the reader who is not completely familiar with this period, a brief summary of the relevant conferences, agreements and treaties is also offered in the Appendix, as well as some short biographical notes. I would like to make it clear, however, that this thesis is neither supposed to be a paraphrase of the Appendix, nor a mere treatise on the commercial relations between the two countries concerned. I aimed rather at revealing the forces behind the events and at illustrating how economic problems became quite often subject to political and military considerations. When trying to attain some understanding of Franco-German relations, it seems advisable to look not only at the interbellum period, but in the first instance to become aware of the currents of history which finally led to the two disastrous World Wars.
Keywords: Economic history -- 1918-1945; France -- Economic conditions -- 20th century; Germany -- Economic conditions -- 20th century; France -- Foreign relations -- Germany; Germany -- Foreign relations -- France